Trial in Absentia in Ethiopia: Legal and Practical Appraisal - Leake Mekonen Tesfay (Mizan law review, 2024)
The trial of a criminal charge may be held in absentia if the accused, duly summoned, fails to appear totally or after s/he was initially present when the trial begins. Ethiopia’s Criminal Procedure restricts trial in absentia to grave crimes and specific fiscal crimes. It also has procedures for summons and retrial. However, it lacks sufficient clarity about issues relating to the partial absence of the accused, the requirement of personal summons, setting aside sentences imposed in absentia, the possibility of rehearing if a defendant fails to appear in appeals by the prosecution and whether an accused may choose representation by defense counsel than standing trial in person. The Cassation Division of the Federal Supreme Court has continued giving binding interpretations that expand the scope of trial in absentia even for minor crimes precluding retrial. Having examined relevant literature and comparative experience, it is suggested that express provisions that address these gaps need to be embodied in the Draft Criminal Procedure and Evidence Law. The Cassation Division should also reconsider its binding interpretations in light of restricting the scope of trial in absentia and towards allowing retrial in cases the accused’s absence for good cause.